(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The aim of this article is to analyze the construction of Mapuche knowledge based on the kimches speech. We argue that within family education, there exists a process of constructing their own knowledge, as a system of knowledge and educational contents for forming individuals. The research methodology applied corresponds to education research. Preliminary results describe the logic of individual educational knowledge from intercultural education in the Mapuche context, so as to contextualize the teaching and learning of Science in schools.